2021
DOI: 10.1016/j.sdentj.2021.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Push-out bond strength and failure mode of single adjustable and customized glass fiber posts

Abstract: Purpose To evaluate the push-out bond strength (PBS) and failure mode of single adjustable (SAP) and customized (CP) posts cemented to root canal dentin using conventional (RelyX Ultimate) or self-adhesive (RelyX U200) dual-cure resin cements. Methods Herein, 40 bovine mandibular incisors were divided into four groups (n = 10): SAP cemented with RelyX Ultimate (SAP-UT), SAP cemented with RelyX U200 (SAP-U2), CP cemented with RelyX Ultimate (CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
6
0
2
Order By: Relevance
“…First, the present study only used one brand of cement system to avoid the complication of comparing different types of cement and to ensure consistent product quality, delivery, and mixing tip system. Previously, the same brand of cement system was used to test the bond strength in bovine teeth, and no difference was observed between RelyX Ultimate with the co-curing procedure and RelyX Unicem, 17 which is consistent with our study's findings. Bitter et al.…”
Section: Discussionsupporting
confidence: 92%
“…First, the present study only used one brand of cement system to avoid the complication of comparing different types of cement and to ensure consistent product quality, delivery, and mixing tip system. Previously, the same brand of cement system was used to test the bond strength in bovine teeth, and no difference was observed between RelyX Ultimate with the co-curing procedure and RelyX Unicem, 17 which is consistent with our study's findings. Bitter et al.…”
Section: Discussionsupporting
confidence: 92%
“…They were all subjected to endodontic treatment and restorative treatment with posts and cores, reproducing a clinical situation. The use of bovine teeth does not affect the mechanical analyses we performed once it has already been shown that bovine and human teeth present similar histological characteristics (Duarte Santos Lopes et al, 2021). Bovine dentin is frequently used for in vitro tests once it presents a similar configuration and histological composition to the human dentin (Da Silva et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Bovine dentin is frequently used for in vitro tests once it presents a similar configuration and histological composition to the human dentin (Da Silva et al, 2010). Moreover, the bovine teeth are more easily obtained, do not present carious lesions and other defects, and their mineral composition is more homogeneous than human teeth (Duarte Santos Lopes et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances have provided options of prefabricated, unpolymerized posts to fit the canals form or in an injectable fashion to eliminate the need for additional tooth structure removal. In such modalities, post-polymerization adhesive and biomechanical properties are the main influential factors of question, where matching drills is irrelevant to their fit [ 9 , 18 , 19 , 20 , 21 , 22 ]. Great research interest for selection of the optimal post type that would exhibit the highest bond strength in a root canal has been advocated, as numerous clinical studies have shown that the most frequent types of failure associated with post restorations of endodontically treated teeth were debonding and loss of retention [ 4 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%